External Antecedents of Entrepreneurial Orientation in Junior High School Students - Ersa Lanang Sanjaya; Jimmy Ellya Kurniawan; Stefani Virlia (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
Several previous studies on entrepreneurial orientation are studied were examined in the bussiness context and show the contribution of internal factors within individuals to the development of entrepreneurial orientation. However, only a few research that focused on entrepreneurship orientation in the context of education, especially for junior high school students in Java Island. This study aims to examine external factors, about authoritative parenting, and creativity climate for the entrepreneurial orientation of junior high school students. The research respondents were 291 junior high school adolescents in Jakarta, Tangerang, Bandung, Yogyakarta, Semarang and Surabaya. Data collection was carried out from August to November 2019. The data were analyzed using multiple regressions. The results showed that there was a significant influence between the authoritative parenting and the creativity climate on entrepreneurial orientation. The role of parents in providing responsible freedom to children allows children to be more courageous in facing risks, innovative, and open to competitive situations. The creative climate at school allows students to express their ideas and get used to solving problems. Keywords: entrepreneurial orientation, authoritative parenting, creativity climate, adolescents, Indonesia